Early experience with the NexGen® CR-Flex Mobile knee arthroplasty system: results of 2-year follow-up - Endres, Stefan (PAGEPress Publications, 2010)
We evaluated our initial results in 57 patients who received the NexGen® CR-Flex Mobile knee system using the standard anterior approach in a prospective study. The bicondylar surface implant was cemented in position (Palacos®) without posterior patellar resurfacing. The clinical outcome and perioperative and post-operative complications were documented over 24 months of its use. Overall, after two years, good results were obtained for the categories of pain and ROM (range of motion), and for the HSS (knee society score) (pre-operative: 42/57; post-operative: 87/80). No pathological radiological findings were made during this period. Two patients, however, felt that the primary operation had not been successful because of lateral patellar tilt. This was corrected with revision surgery. It was remarkable that our patients achieved greater than 100° flexion within the first 14 days of the immediate post-operative period. Evaluation and comparison of the scores with those of conventional bicondylar surface replacement systems showed no relevant differences.